Penentuan Jenis dan Konsentrasi Pelarut untuk Isolasi Zat Warna Kulit Buah Manggis (Garcinia mangostana L) - Amin Fatoni; Mando Hastuti; Dwi Agustina V; Suwandri Suwandri (Molekul, 2008)
Natural pigment recently have interest to explore to reduce synthetic chemical effect for organism and environment. Mangostine (Garcinia mangostana L) is one of tropical fruit that have peel strong pigment, thus potent as new natural pigmen. Solvents including water, ethanol and methanol applied to extract mangostine peel pigment. The best solvent determined by measuring pigment filtrate using spectrophotometer. The highest absorbance data indicated the best solvent, i.e. more extract yielded by this solvent. The optimum concentration of the solvent for best extraction also investigated with the same procedure above, and finally the natural pigment obtained identified using paper chromatography. The best solvent investigated for extraction was ethanol at concentration 70%. The pigment extracted from mangostine peel proposed as pellargonidine 3-glycoside group of anthocyanin